Capital adequacy of the banking industry in Indonesia - Sri Murtiyanti; Noer Azam Achsani; Dedi Budiman Hakim (Economic Journal of Emerging Markets)
This study analyzes the relationship between credit risk and profitability on the capital adequacy ratio (CAR) of commercial banks in Indonesia. The empirical model result shows that credit risk and profitability performance altogether significantly influence the capital adequacy ratio (CAR). Partially, the variables that significantly influence the CAR are the characteristics and complexity of the bank group. This study also suggests that the pace towards the long-term balance is, in general, less than one year. Capital ratio in the banking industry is 8%, indicating the bank has set aside to anticipate the impact of external factors as well as to comply with Bank Indonesia Regulation Number 15/12/PBI/2013.